CPT has 'linked up with Burma groups' - (:unkn) unknown (My University, 1990)
The Communist Party of Thailand (CPT) has joined the Burmese Communist Party (BCP) and minority groups inside Burma operating on the western border of Thailand, according to a former CPT member who recently defected to the authorities in the Northeast.
Item submitted with minimal metadata and description. If you have additional information you can provide please contact rworks [at]uw [dot]edu, include the URI address below and any information you have. UW access only
Keywords: Communist Party of Burma; Communist Party of Thailand